Collaborative school leadership in integrating the Merdeka Curriculum with extracurricular activities: A case study of SMA Negeri 3 Jambi - Muspawi, Mohamad; Restalillah, Rida Restu; Lunita, Pramodya Casqie; Safitri, Mayada (Jurnal Pembangunan Pendidikan: Fondasi dan Aplikasi, 2024)
This study aims to analyze the role of collaborative leadership practiced by the principal in integrating the Merdeka Curriculum with extracurricular activities at SMA Negeri 3 Jambi City. Employing a qualitative phenomenological approach, data were collected through interviews, observations, and documentation, with participants selected using purposive sampling. The findings reveal that the principal plays a central role in ensuring the alignment between the Merdeka Curriculum and extracurricular programs by engaging teachers, students, and external partners through collaborative leadership practices. The principal motivates and involves teachers as extracurricular advisors, coordinates pedagogical and extracurricular units to maintain coherence, facilitates partnerships and resource allocation, and establishes supportive policies to enhance student participation. Furthermore, collaborative strategies—such as shared decision-making, open communication, and structured coordination—enable the school to create an environment that supports students’ talents, interests, and character development in accordance with the principles of the Merdeka Curriculum. This study highlights that collaborative leadership is essential for strengthening curriculum–extracurricular integration and for realizing comprehensive and student-centered learning within the framework of educational transformation in Indonesia.